2003
DOI: 10.1016/s1054-3139(03)00098-5
|View full text |Cite
|
Sign up to set email alerts
|

An ecosystem model of food web and fisheries interactions in the Baltic Sea

Abstract: Because fisheries operate within a complex array of species interactions, scientists increasingly recommend multispecies approaches to fisheries management. We created a food web model for the Baltic Sea proper, using the Ecopath with Ecosim software, to evaluate interactions between fisheries and the food web from 1974 to 2000. The model was based largely on values generated by multispecies virtual population analysis (MSVPA). Ecosim outputs closely reproduced MSVPA biomass estimates and catch data for sprat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 29 publications
1
77
1
Order By: Relevance
“…For example, both the RTI and the Ecosim model sensitivity analysis (steps 3 and 4) imply that cod is the most important food-web structuring group in the Baltic Proper. In contrast to some previous studies (Harvey 2003;Casini et al 2009;Möllmann et al 2009), however, our results do not readily support the hypothesis that changes in the adult cod biomass directly act as the foremost pelagic ecosystem structuring mechanism. Most of our models, including the original, indicate bottom-up control between sprat and adult cod (Fig.…”
Section: Food-web Functioncontrasting
confidence: 99%
“…For example, both the RTI and the Ecosim model sensitivity analysis (steps 3 and 4) imply that cod is the most important food-web structuring group in the Baltic Proper. In contrast to some previous studies (Harvey 2003;Casini et al 2009;Möllmann et al 2009), however, our results do not readily support the hypothesis that changes in the adult cod biomass directly act as the foremost pelagic ecosystem structuring mechanism. Most of our models, including the original, indicate bottom-up control between sprat and adult cod (Fig.…”
Section: Food-web Functioncontrasting
confidence: 99%
“…Cod, herring and sprat dominate fisheries in the Baltic Sea (Sparholt 1991;Heikinheimo 2011) and are key components of Baltic Sea food web models (Harvey et al 2003). These food web models are highly sensitive to changes in cod and sprat abundances , suggesting that the effects of ocean acidification on these species may have more far-reaching consequences than for other components of the Baltic Sea food web.…”
Section: Fishmentioning
confidence: 99%
“…Recent correlative analyses have demonstrated that overfishing of top predators may have resulted in changes to food web structure in the Northwest Atlantic (Frank et al 2005) and Baltic pelagic ecosystems (Harvey et al 2003, Österblom et al 2007, Casini et al 2008, which may partly explain the general increase in primary production observed in these systems. Similar to the NW Atlantic and Baltic situations, large-scale declines in the abundance of top predatory gadoid species have also been documented on the Swedish west coast bordering the Skagerrak and Kattegat Sea, presumably as a result of overfishing (Svedäng & Bardon 2003).…”
Section: Introductionmentioning
confidence: 99%